Moving From the Margins: Culturally safe teacher education in remote northwestern British Columbia - Harrison, Edward; Lautensach, Alexander; McDonald, Verna (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2012)
In 2007 the University of Northern British Columbia initiated a two-year elementary teacher education program at the Northwest Campus in Terrace, British Columbia. The program was designed to meet specific community needs in the North that arise from inequities in the cultural safety of Indigenous teachers and students. The authors share three collegial inquiries into the program’s contribution toward improving cultural safety in K-12 schools and meeting social justice challenges in the region’s communities. Culturally safe allocation of space became better understood, affective learning outcomes were recognized as important determinants of cultural safety, and teacher action in classrooms towards cultural safety was scaffolded for various settings.